Transcriptional profiling of early differentiation of primary human mesenchymal stem cells into chondrocytes - Thomas Schwarzl; Andrea Keogh; Georgina Shaw; Aleksandar Krstic; Elizabeth Clayton; Desmond G. Higgins; Walter Kolch; Frank Barry (Scientific Data, 2023)
Abstract Articular cartilage has only very limited regenerative capacities in humans. Tissue engineering techniques for cartilage damage repair are limited in the production of hyaline cartilage. Mesenchymal stem/stromal cells (MSCs) are multipotent stem cells and can be differentiated into mature cartilage cells, chondrocytes, which could be used for repairing damaged cartilage. Chondrogenesis is a highly complex, relatively inefficient process lasting over 3 weeks in vitro. Methods: In order to better understand chondrogenic differentiation, especially the commitment phase, we have performed transcriptional profiling of MSC differentiation into chondrocytes from early timepoints starting 15 minutes after induction to 16 hours and fully differentiated chondrocytes at 21 days in triplicates.